Development of methods for the control of fusarium wilt and crown rot on tomato - Almasrahi, Ali (2020)
Fusarium oxysporum (Fo) is a major pathogen that causes economic losses of many important crops around the world and affects a very wide range of plants including tomato. Fusarium oxysporum f.sp. lycopersici (Fol) that causes fusarium wilt disease and Fusarium oxysporum f.sp. radicis-lycopersici (Forl) which is the causal agent of crown and root rot disease are considered amongst the most devastating pathogens on tomato plants (Solanum lycopersicum L.). The use of UV-C seed treatments, silicon and biocontrol agents are considered as safe and potential options for controlling plant diseases. This study focused on the evaluation of low doses (0, 2, 4 and 6 kJ/m2) of Ultraviolet light (UV-C) on disease development of Fol and Forl. The results showed that there were signiﬁcant reductions in disease severity for plants grown from UV-C-treated seeds when inoculated with Fol or Forl. For Fol, The percentage disease severity score was decreased from 87.5% (control) to 75.0% and 66.6% with 13.71% and 23.88% respectively, whilst a 6 kJ m-2 dose signiﬁcantly reduced Forl severity from 69.4% (control) to 50.0%. The results showed that there was a correlation between the reduction in the disease severity by UV-C seed treatments (4 and 6 kjm-2) and the DNA quantity in the root, crown and stem samples for Fol and Forl. The inhibitory potential of sodium silicate against Fol and Forl was investigated under in vitro and in vivo conditions. Under laboratory conditions, the higher concentrations (30, 40 and 50 mM) showed significant reduction in the mycelial growth of both Fol and Forl. The 30, 40 and 50 mM concentrations recorded 57.23, 73.77 and 96.25% reductions for Fol, and 46.25, 81.99 and 97.73% for Forl respectively. In in vivo experiments, 30, 40, and 50 mM concentrations were highly significant compared to the other treatments. The disease severity was 56.0, 50.0, and 46.6% respectively for Fol whilst for Forl, the disease severity was 45.83, 41.66, and 29.16% respectively. The expression of some pathogen related genes, GluA (acidic extracellular b-1,3-glucanase), GluB (basic intracellular b-1,3-glucanase), Chi3 (acidic extracellular chitinase), Chi9 (basic intracellular chitinase), PR-1a (PR-1 protein isoform PR-P6) and PAL (phenylalanine ammonia-lyase) induced in tomato by UV-C, sodium silicate, Trichoderma spp. and the combination of these treatments against Fol and Forl have been investigated. The results showed that the expression of all tested genes was varied in all treatments. However, they were significant compared to the control. The combination treatment recorded high accumulation of all tested genes compared to other treatments. LeChi3 and LeChi9 accumulation were higher in roots samples in plants inoculated with Fol, whilst in plants inoculated with Forl, LeChi3, LeChi9 and LePR1a accumulation were higher in root and crown samples. In conclusion, UV-C seed treatments combined with sodium silicate have been shown to be an effective disease control option that could contribute to induced disease resistance to Fol and Forl pathogens of tomato.